The Importance of Holistic Education for Early Childhood: Integrating Cognitive, Emotional and Social Aspects - Iis Rodiah; Gayuk Zulaika; Dedi Gunawan Saputra (Journal of Gemilang, 2024)
Early childhood education (ECE) plays a fundamental role in children's development, which is not only limited to cognitive aspects, but also includes emotional and social development. Holistic education at an early age integrates these three aspects simultaneously, giving children the opportunity to develop optimally in various dimensions. Thus, a holistic approach in early childhood education is considered crucial in creating a strong foundation for further development. This article aims to analyze the importance of holistic education, as well as how the integration of cognitive, emotional, and social aspects can affect children's overall development. Through a Systematic Literature Review (SLR) research approach, this article examines various previous studies on holistic education for early childhood, focusing on the relationship between education that emphasizes cognitive, emotional, and social development. This study shows that the integration of these three aspects not only enriches children's learning experiences but also plays a role in improving their psychological and social well-being. Therefore, holistic education is a very relevant model to be applied in early childhood education institutions to support optimal development in the future.